Digitization of Mariemma's legacy audiovisual collection: The challenge of preserving intangible heritage - Díaz-Emparanza Almoguera, Miguel (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article analyzes the digitization process and the difficulties encountered along the way, as a project that involved audiovisual technicians, academic researchers, and a famous Spanish dancer’s legacy: the audiovisual documents Guillermina Martínez Cabrejas, Mariemma, left to a museum located in her hometown. The specific criteria used to decide on the differences that arose in the process, provides great results and, also, a critical view on the limitations of the international preservation guidelines of digital objects.